Avaliação da implantação do plano diretor de atenção primária à saúde sob a ótica de enfermeiros: contribuições da nova economia institucional - Bittencourt, Tatiana Oliveira Silva (2014)
This research is characterized as a qualitative study, descriptive, exploratory, conducted with the nurses of the Primary Health Care (PHC) in the municipality of Itajubá/MG, which aimed to verify the general conception that these professionals possess about the Master Plan of Primary Health Care (PDAPS) and specific objectives and identify the difficulties encountered by these facilities in the deployment of nurses PDAPS as well as identify the transaction costs that were present this process. The survey was conducted with eleven (11) of the nurses who participated in the APS deployment PDAPS in said county and working in units of the Family Health Strategy (FHS), Basic Health Unit (BHU) traditional and UBS reorganized by ESF, all located in the urban area. The sample was intentional and the sample size determined by data saturation criterion. Participants underwent a structured interview containing questions relating to personal and professional characteristics and deployment PDAPS and a semi-structured interview satisfaction two questions relating to the design of the nurse about PDAPS and facilities and difficulties that were present in the same deployment. The data were discussed from the thematic content analysis in the present. Process analysis and the theoretical framework used in this study revealed three (3) dimensions: design of nurses regarding PDAPS, facilities in using the second PDAPS nurses and difficulties in implementing the second PDAPS nurses. These dimensions emerged seven (7) categories and seventeen (17) sub - categories. In relation to nurses' conceptions about PDAPS, it was observed that for all respondents, this plan is directly related to the reorganization and standardization of health services in PHC. Overcome the difficulties in implementing the facilities, and for five (5) respondents there was no facility in this implementation process. Regarding facilities, we identified four (4) facilities and what stood out was in relation to commitment and quality in the transfer of workshops by facilitators. In the field of the difficulties identified nine (9) difficulties that permeated this process, and the lack of professional commitment, the monitoring of the bureaucracy, the human resources and insufficient staffing disqualified the biggest hindering the realization of this plan. From the theoretical framework of New Institutional Economics were raised costs in the execution and implementation of PDAPS which were transaction costs of agency, informational and political, and the cost of agency obtained a prevalence of 100 % in every speech. These data indicate the need for improving the management of health services in the core network in the city of Itajubá/MG, as well as the development of an incentive system that encourages professional motivation and rescue the credibility of the primary care in health that municipality. Despite the difficulties encountered, the nurses understood the proposal PDAPS and showed interest in their implementation from the awareness that primary health care in this city needs a systemic reorganization so that they can offer a quality service to the population.